Networks, work, and inequality - McDonald, Steve (Research in the sociology of work ;, 2013)
The importance of social relationships at work has long been recognized in the social sciences. Interest in this topic has been renewed through scholarly and popular discussions of social capital as well as recent innovations in network data collection and analysis. These developments have allowed researchers to ask a variety of new questions about the role of networks in the world of work and a multitude of approaches to answering those questions. While several monographs have been written on issues related to networks and work, none has simultaneously brought together the range of approaches used to explore this topic. Furthermore, this volume is the first to merge this focus on networks and work with a sociological perspective on inequality. Specifically, the chapters illuminate the processes by which social networks in work organizations can effectively generate, sustain and ameliorate social inequalities across individuals, firms, and occupational fields. In doing so, this volume offers valuable insights that inform researchers and policy makers alike regarding issues of workplace discrimination, diversity and innovation.